Incidental Detection of Precancerous and Malignant Gall Bladder Lesions in Routine Cholecystectomy Specimens: A Retrospective Study of 3 Years - Jain, Pooja; Sharma, Swati; Pai, Kanthilata (Annals of Pathology and Laboratory Medicine, 2019)
Background & Objectives: Gallbladder dysplasia (GBD) and adenoma are premalignant lesions, which may progress to carcinoma through different pathways. Gall bladder (GB) neoplasms are relatively uncommon and are usually asymptomatic during early stages. We analyzed the clinico-pathological features of precancerous and malignant gallbladder lesions in routine cholecystectomy specimens and studied the association of mucosal metaplasia and gall stones with GB adenoma, dysplasia and carcinoma. Materials & Methods: This is a 3 year retrospective study where histopathology proven cases of GBD, adenomas and carcinomas were retrieved from Pathology database from January 2012 to December 2014. The clinical details and histopathological features of these cases were studied and analyzed. Results: Out of total 2200 cholecystectomy specimen studied, 7 cases of GBD, 5 cases of adenoma and 10 gallbladder carcinomas (GBC) were identified. Out of total 22 patients, 11 were females. Predominant clinical feature was pain in 86% cases. On ultrasonography (USG), majority showed cholelithiasis. Cholecystectomy was performed in all predominantly due to cholecystitis and lithiasis. On microscopy, 43% cases of dysplasia showed high grade features, 60% cases of adenoma showed tubular type with pyloric metaplasia and 50% of GBC were moderately differentiated. Associated dysplasia in GBC was noted in 50% and associated metaplasia in 60% cases. Follow up ranged from 2-4.5 years. 40% GBC showed lymph node involvement and 20% showed distant metastasis. Conclusion: All cholecystectomy specimens should definitely be sent for histopathologic evaluation to detect unapparent GB lesions. Early detection of these lesions may lead to good prognosis and prolonged survival.